Perspektif Hukum Islam Terhadap Jual Beli Diamond Pada Game Online Mobile Legends Via Online (Studi Kasus di Toko Online Diamond Mobile Legends “Kiming Store”) - Muslihin, Nasrulloh Jundi; Muti, Ahmad; Saputra, Refki (Journal of Student Development Informatics Management (JoSDIM), 2023)
Diamond transactions involve steps such as contact through social media or WhatsApp, choose diamond package, provide account information games, make payments, send proof of transfer, and receive diamonds after payment. There is also a list of diamond prices based on quantity. This thesis analyzes aspects of diamond buying and selling transactions from an Islamic perspective. Diamond buying and selling transactions in the online game Mobile Legends seen from perspective of Islamic law, where the pillars and conditions of buying and selling transactions are observed, including consideration of greeting contracts that allow for postponement of delivery goods. This transaction is considered valid if it meets these criteria. However, There is debate among Islamic scholars about the laws of playing games on line. Some consider it prohibited if they neglect their obligations and detrimental to one's productivity, while others consider it permissible as a form of entertainment. The research also warns of potential risks addicted to playing games. The conclusion of this research states that selling buying diamonds in the online game Mobile Legends is acceptable in view Islam as long as it complies with the principles of the sale and purchase agreement and does not violate the principles of Islamic law. However, this research also warns of dangers potential addiction to playing games